2021
DOI: 10.1002/sej.1400
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of customer ties and industry segment maturity on business model adaptation in an emerging industry

Abstract: Research Summary Why do some young firms change their business models while others do not? Why do some firms make small changes, while others make more substantial changes? And does industry context matter? Drawing on organizational learning theory and utilizing a unique database tracking 187 young firms through the first decade of the mobile health industry, we examine the role of customers in young firms' business model adaptation. We find a positive impact of customer portfolio breadth (capturing the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 102 publications
0
23
0
2
Order By: Relevance
“…Although it is easier to imagine a real options reasoning approach in established firms engaged in the process of starting up new ventures (de alio), it is important to consider the notion of a portfolio of opportunities (requiring hypothesis testing) for independent startups (de novo). For example, Denoo et al (2018) found that startups with broader portfolios of customers engage in more business-model changes and changes of a greater degree. Generally, future research can explore the extent to which independent startups have portfolios of potential opportunities; what form the hypotheses take to test these potential opportunities; and how the different hypotheses relate to each other in terms of their formation, information gathered, and analyses of findings.…”
Section: Building Block 1: Finding and Prioritizing Market Opportunitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is easier to imagine a real options reasoning approach in established firms engaged in the process of starting up new ventures (de alio), it is important to consider the notion of a portfolio of opportunities (requiring hypothesis testing) for independent startups (de novo). For example, Denoo et al (2018) found that startups with broader portfolios of customers engage in more business-model changes and changes of a greater degree. Generally, future research can explore the extent to which independent startups have portfolios of potential opportunities; what form the hypotheses take to test these potential opportunities; and how the different hypotheses relate to each other in terms of their formation, information gathered, and analyses of findings.…”
Section: Building Block 1: Finding and Prioritizing Market Opportunitiesmentioning
confidence: 99%
“…From the perspective of business models as a firm attribute (Massa et al, 2017), the focus is on existing firms-not the creation of a new independent firm. Although we have a good understanding of firms that are strategically oriented toward entrepreneurship (Covin & Slevin, 1991;Lumpkin & Dess, 1996;Wiklund & Shepherd, 2005) and why some firms are better at creating corporate new ventures (de alio) than others (Covin et al, 2018), there is an insufficient understanding of the activities associated with the different business-model attributes (Massa et al, 2017; for an exception, see business-model change by Denoo et al, 2018). Indeed, applying the practice term-namely, focusing on what people do-of strategy (McDonald & Eisenhardt, 2014;Snihur & Zott, 2019;Whittington, 2006) and social theory (Brown & Duguid, 2001;Orlikowski, 2002) to firms' business models will make an important contribution to entrepreneurship.…”
Section: Building Block 2: Designing Business Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach can facilitate adaptation to the external environment. For example, startups with broader portfolios of customers engage in more business-model changes and changes of a greater degree (Denoo et al, 2018). These business-model changes are often critical for startup performance in highly uncertain environments.…”
Section: Building Block 1: Identifying and Evaluating Market Opportunitiesmentioning
confidence: 99%